(Under)cover and Uncovered: Muslim Women's Resistance to Islamophobic Violence - Baboolal, Aneesa A. (Victims & offenders, 2024)
After 9/11, research highlighted how Muslim communities endured discrimination, surveillance, and violence. In recent years, few studies have critically assessed how gender-based harassment of Muslim women is simultaneously linked to hypervisibility (veiling), while “invisible” (non-veiled) Muslim women remain susceptible to verbal harassment and physical violence in the public sphere. Drawing from qualitative in-depth semi-structured interviews with Muslim women (n = 27) across racial/ethnic and immigrant identity, this article examines the unique vulnerability of Muslim women during the Trump presidential administration, including covert and overt forms of violence. Findings indicate myriad forms of violence as veiled women navigate harassment at the axes of racialized Muslim identity and social categorization as immigrants (twice racialized intersectionality). Yet, Black Muslim women’s experiences are further complicated by anti-Black racism. Muslim women navigate gender-based anti-Muslim bias by disrupting notions of passive victimhood by leaning into invisible or hypervisible markers, revealing or concealing their ethnoreligious identity through racial ambiguity, and engaging in advocacy.